Taxation and Corporate Pension Policy - Tepper, Irwin (Journal of Finance, 1981)
As a result of rapid growth in the post—war period, pension plans have become a major component of the financial structure of large corporations. A recent survey [5] of 475 of the Fortune 500 companies revealed that pension cost in 1978 averaged 12.5 % of pretax profits and 7.2 % of